2021
DOI: 10.1002/tal.1860
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of wind pressure fluctuating characteristics and wind load shape factor of long‐span cylinder roof structure

Abstract: Summary This paper comprehensively presents the results of a wind tunnel experiment of the wind pressure fluctuating characteristics of a long‐span roof structure, namely the fluctuating wind pressure coefficient (FWPC), wind pressure power spectrum, and wind pressure coherence. The variation trend of FWPCs in the wind directions of 0°, 45°, and 90° were analyzed in sealed and open conditions, as well as the fluctuating wind pressure coefficients of lateral and longitudinal profiles of roof. Subsequently, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Due to the limited space, Figure 7 only presents the contours of model parameters on long‐span tri‐centered cylindrical roof under 0° wind direction. Wu et al investigated the wind pressure fluctuating characteristics for this structure, [ 5 ] so it can be found that the distribution characteristics of wind pressure spectra parameters are consistent with the fluctuating wind pressure distribution, indicating that the spectra parameters can reflect the wind pressure fluctuating characteristics of each flow field area. Especially, the peak frequency Fm is related to the reduced vortex shedding frequency.…”
Section: Wind Pressure Spectrum Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…Due to the limited space, Figure 7 only presents the contours of model parameters on long‐span tri‐centered cylindrical roof under 0° wind direction. Wu et al investigated the wind pressure fluctuating characteristics for this structure, [ 5 ] so it can be found that the distribution characteristics of wind pressure spectra parameters are consistent with the fluctuating wind pressure distribution, indicating that the spectra parameters can reflect the wind pressure fluctuating characteristics of each flow field area. Especially, the peak frequency Fm is related to the reduced vortex shedding frequency.…”
Section: Wind Pressure Spectrum Modelmentioning
confidence: 95%
“…[2] However, the separation flow and reattachment lead to the significant non-Gaussian characteristics of the wind pressure in the local zones, such as the windward edge, roof corner, and leeward side, leading to an obvious increase in the peak factor. [3][4][5][6][7]…”
mentioning
confidence: 99%
“…Under the action of unsteady wind, the response of the building to wind load is also unsteady. This means that the amplitude of the vibration the structure produces in response to wind load changes over time, as does the frequency of its vibration [5]. On this basis, wind load is highly likely to cause the internal resonance of HRB structures, resulting in structural destruction and serious safety accidents.…”
Section: Unsteadiness Of Wind Frequencymentioning
confidence: 99%